An Empirical Investigation Into The Influence Of Selected War Events On Herd Mentality And Its Implications For Market Volatility In The National Stock Exchange Of India (NSE) - Dr. Urvi Amin; Dr. Swati Saxena; Dr. Shivanisinh Parmar (Educational Administration: Theory and Practice, 2024)
The enigmatic connection between herd mentality and market volatility is the subject of this study, which utilizes the National Stock Exchange of India (NSE) as a setting for its empirical examination. Specifically, the research examines the impact of selected war events on the NSE, assessing the extent to which such events trigger herd behaviour among investors and consequently exacerbate market fluctuations. A rigorous econometric framework is employed to analyse a comprehensive dataset encompassing historical stock market data and relevant war events. The findings illuminate the intricate interplay between war-induced uncertainty, investor sentiment, and herd behaviour, providing valuable insights into the dynamics of market volatility in the aftermath of geopolitical tensions.